Brain targeted delivery of lurasidone HCl via nasal administration of mucoadhesive nanoemulsion formulation for the potential management of schizophrenia. (13th September 2020) - Patel, Mrunali R.; Patel, Rashmin B.; Thakore, Shivam D.; Solanki, Ajay B.
Abstract: This investigation aimed to design, develop, and optimize intranasal nanoemulsion for brain targeted delivery of lurasidone hydrochloride for the management and treatment of schizophrenia. The design of experiment supported optimization of high-pressure homogenization (HPH) process was executed for the manufacturing of lurasidone loaded nanoemulsion. The nanoemulsion comprising of lurasidone hydrochloride (10 mg/mL), 20% Oilmix, 25% surfactant and, 55% aqueous phase (w/w) was processed with HPH at optimized conditions to get droplet size in the nano range. The droplet size of optimized nanoemulsion was found to be 48.07 ± 3.29 nm with a polydispersity index of 0.31 ± 0.01. The optimized translucent nanoemulsion (% transmittance of 88.56 ± 2.47) was found to be non-toxic to sheep nasal mucosa and stable for six months. The results of ex vivo diffusion study revealed the improvement in drug diffused by mucoadhesive nanoemulsion (MLNE) (1.41 × 10 −4 ± 1.11 × 10 −5 cm 2 /min) as compared to the solution (1.15 × 10 −4 ± 1.35 × 10 −5 cm 2 /min). The results of pharmacodynamic studies in mice uncover the highest inhibition of compulsive behavior (64.63%) and spontaneous locomotor activity (60.87%) shown by MLNE. This may be due to increased bioavailability in a brain, and possibly confirms the potential of nanoemulsion in targeting the brain through nasal route in the treatment of schizophrenia.